Multiresidue determination of pesticides in olive and palm oil by LC-QTOF-MS / Elham Sobhanzadeh - Sobhanzadeh, Elham (2011)
In this study a comprehensive evaluation of two efficient sample treatment methods based on LLE/freezing-out coupled with matrix solid-phase dispersion-sonication (UA-MSPD) and precipitation at low temperature followed by dispersive solid-phase extraction (d-SPE) has been performed for determination of dimethoate, malathion, carbaryl, simazine, terbuthylazine, atrazine and diuron in both olive and palm oil using liquid chromatography time-of-flight mass spectrometry (LC-QTOF-MS) and electrospray as the ionization source. Identification and confirmation of the compounds were based on retention time matching along with the accurate mass measurements of the protonated molecules ([M+H]+) and their main fragment ions. Typical electrospray ionization parameters such as nebulizer and drying nitrogen flow rates, drying gas temperature and capillary voltage as well as fragmentor voltage which affecting the performance of LC-TOF-MS were carefully studied. Optimization approaches were studied in terms of LLE/LTP to select efficiency of type and volume of extracting solvent with and without LTP to obtain the highest recovery yield of pesticides and the lowest co-extract fat residues in the final extract, UA-MSPD clean-up conditions to select type and amount of both dispersant and clean-up sorbent as well as to evaluate the extraction condition from the point of with or without sonication, finally d-SPE cleanup to choose nature and value of clean-up sorbent. The optimal conditions for UA-MSPD were obtained using 5 g of palm oil, 750 mg of PSA as dispersing sorbent, 250 mg of florisil as clean up sorbent and 15 mL of acetonitrile as eluting solvent under conditions of 15 min ultrasonic bath at room temperature. However, when d-SPE was used as the clean-up procedure, high recoveries and good sensitivity were obtained with 150 mg PSA and 50 mg GCB (PSA: GCB (3:1 w/w)).